In vitro enzyme inhibitory properties, antioxidant activities, and phytochemical fingerprints of five Moroccan seaweeds - Grina, Fatiha; Ullah, Zain; Kaplaner, Erhan; Moujahid, Abderrahman; Eddoha, Rabiaa; Terzioğlu, Pınar (Elsevier, 2020)
The coastlines of Morocco have an abundant resource of diverse seaweeds but the bioactivity of many of these seaweeds is still unexplored. The aim of this study was to contribute to the evaluation of the antioxidant potential, using different in vitro systems and searching some fingerprints of phenolic constituents based on LC-MS/MS method of five seaweeds species obtained from Moroccan Atlantic Ocean: Bifurcaria bifurcata, Cystoseira humilis, Cystoseira stricta, Fucus spiralis and Gelidium sesquipedale. The total phenolic compounds, the antioxidant activity, anticholinesterase, tyrosinase inhibitory, urease inhibitory activities and the organic compounds were determined. The results showed that Fucus spiralis possessed the highest phenolic and flavonoid contents compared to the others. In addition, Fucus spiralis (IC50: 13.25 +/- 0.9 mu g/mL) and Cystoseira stricta (IC50 : 13.58 +/- 1.2 mu g/mL) exhibited higher lipid peroxidation inhibitory activity. The highest1,1-diphenyl-2-picrylhydrazyl (DPPH) (IC50 : 47.23 +/- 3.8 mu g/mL), 2,2'-azino-bis (3-ethylbenzothiazo-line-6-sulfonic acid) dia-mmonium salt (ABTS) (IC50 : 5.95 +/- 0.6 mu g/mL), and Cupric reducing antioxidant capacity (CUPRAC) (55.24 +/- 0.04 mu g trolox equivalents/mg) activity was measured in Fucus spiralis. Regarding metal chelating activity, Bifurcaria bifurcata was the best (IC50 : 45.22 +/- 0.9 mu g/mL) compared to the others. The highest acetylcholinesterase (IC50 : 28.92 +/- 1.8 mu g/mL), butyrylcholinesterase (IC50 : 11.72 +/- 2.8 mu g/mL), tyrosinase (IC50 : 6.19 +/- 0.4 mu g/mL) and urease (IC50 : 10.96 +/- 1.3 mu g/mL) inhibitory activities was found in Fucus spiralis. According to LC-MS/MS results, quinic acid, malic acid, fumaric acid, gallic acid, protocatechuic acid, 4-OH-benzoic acid, hesperidin, were detected in ethanol extracts of the five Moroccan seaweeds. This study demonstrated that seaweeds, particularly Fucus spiralis and Cystoseira stricta could be a promising source of antioxidants and phytochemicals which can be used in cosmetics, pharmaceutical and as nutritional food supplement in food industries to deleterious free radical induced stress, disorder and diseases. (C) 2019 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Macroalgae; Phenolics compounds; Seaweed extracts; Antioxidant activity; Enzymatic activity; LC-MS/MS method